Development of a Web-Based Spare Parts Inventory System Using the First-In, First-Out Method and Acceptance Analysis Based on the Unified Theory of Acceptance and Use of Technology - Adam Firdaus; Cempaka Ananggadipa Swastyastu; Ratna Nur Tiara Shanty (Department of Information Systems and Technology, Faculty of Intelligent Electrical and Informatics Technology, Universitas 17 Agustus 1945 Surabaya, 2025)
As a service-oriented company, Jaya Sentosa faces significant challenges in managing its spare parts inventory, leading to resource inefficiencies. Key issues include documentation discrepancies, inventory inconsistencies, and inadequate monitoring mechanisms. To address these problems, this study designs and implements a web-based information system, referred to as SIWEB-JS, aimed at enhancing inventory accuracy and operational efficiency. The system was developed using the Rapid Application Development (RAD) approach, adopting the First-In, First-Out (FIFO) principle, and built with PHP using the CodeIgniter v4.4.4 framework, supported by a MySQL database. System functionality was evaluated through Black-Box Testing, while user acceptance was assessed using the Unified Theory of Acceptance and Use of Technology (UTAUT). The results indicate that SIWEB-JS effectively records real-time transactions, maintains accurate inventory levels, and improves data accessibility. The implementation of FIFO contributed to better inventory governance. Furthermore, the UTAUT-based evaluation revealed that Performance Expectancy (PE), Effort Expectancy (EE), and Social Influence (SI) significantly influenced Behavioral Intention (BI), suggesting that the system is perceived as useful, user-friendly, and well-supported by users.